Distinctive Contemporary Voice: Liberal Islam Thought in Indonesia - Giora Eliraz (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
This paper aims to turn attention to an intriguing stream of thought in the multi-faceted and plural Islamic discourse in Indonesia, a home to the largest Muslim community in the world. This stream of thought in Indonesia attempts to connect Islamic doctrine, belief, thinking and knowledge with basic liberal themes such as separation between religion and politics, pluralism, freedom of thought, democracy, progress, human rights, gender equality and interfaith dialogue. Similarly, it also seeks to reinterpret the formative sacred texts through liberal paradigm and through contemporary context.DOI: 10.15408/sdi.v15i3.523